An Overview of SAARC National Libraries - Satija, M. P.; Chander, Harish; Singh, Prerna (Journal of Information and Knowledge, 2018)
The paper highlights the functions of a national library as viewed by some authorities in the field. The history, objectives, building, collection and services of the national libraries of SAARC nations are examined. The picture that emerges is that national libraries in the SAARC region are victims of neglect, political interference in administration and lack of understanding of the importance of a repository of national documentary heritage.